Solid base catalyzed depolymerization of lignin into low molecular weight products - Chaudhary, Richa; Dhepe, Paresh Laxmikant (Green Chemistry, 2017)
For the biorefinery concept to become commercially viable, it is essential to add value to lignin which is the only naturally available aromatic polymer. A one-pot depolymerization of lignin into reactive substituted phenolic compounds (platform chemicals and octane enhancers) with low molecular weight is of paramount importance and for that, the development of an environmentally benign method is necessary. Herein we report the depolymerization of high molecular weight lignin (60 000 Da) over various recyclable solid base catalysts at 250 degrees C over 1 h. Under these conditions, most of the zeolitic catalysts (NaX, NaY, NaP) showed very high yields of low molecular weight products compared to other catalysts (MgO, CaO, HT, HAP). But in particular, over NaX the maximum yield (51%) of low molecular weight products was achieved. Identification and quantification of products was done by GC, GC-MS, HPLC, LC-MS, CHNS, NMR and FT-IR techniques. The revelation of retention of most of the functional groups on products present in lignin was confirmed by FT-IR studies. It is observed that the efficiencies of catalysts were dependent on pH, the cation, the type and concentration of basic sites, etc. A unique study on the product adsorption capacities on solids was done and it is recognized that as the strength of basic sites increases, adsorption enhances.

Depolymerization of lignin using a solid base catalyst - Chaudhary, Richa; Dhepe, Paresh L. (Energy & Fuels, 2019)
Lignin extraction from lignocellulosic biomass has attracted considerable attention for an alternative production of sustainable fuels and chemicals. We report the lignin isolation from coconut coir using Klason, organosolv, and soda methods and the depolymerization of isolated lignin to value-added chemicals using a solid base catalyst. The yield of isolated lignin by the Klason method was found to be about 4 to 6 times higher than that by other methods. The structure of isolated Klason lignin (CC-KL), organosolv lignin (CC-ORGL), and soda lignin (CC-SL) was studied using attenuated total reflection (ATR), NMR, microanalysis, and so forth. The monomer molecular formula derived from microanalysis suggested that coir lignin is rich in guaiacyl units. ATR and C-13 NMR clearly indicate that CC-ORGL contains more C-C bonds compared to CC-KL and CC-SL. Subsequently, these isolated lignins were depolymerized over a solid base catalyst (NaX) under atmospheric pressure. CC-SL shows a high yield of aromatic products (28%) compared to CC-ORGL and CC-KL. In order to develop a sustainable future technology, one-pot depolymerization of coconut coir was performed which resulted in a high yield (64%) of aromatic products.

Upgrading lignin derived monomers over basic supported metal catalysts - Chaudhary, Richa; Dhepe, Paresh L. (Fuel, 2021)
Catalytic upgradation of aromatic monomers derived from lignin depolymerization is of high interest for the production of sustainable fuels and chemicals. Basic support has potential to provide advantages of better substrate-support interaction and reduced coke formation. Hence, we report the effect of various basic supports for metal catalysts (Pt, Pd, Ru) on the upgradation of phenol, guaiacol and eugenol. The complete hydrogenation product is achieved due to the strong interaction of the substrate with catalyst. Phenol is converted (55%) into cyclohexanol (49% yield) with low loading of Pt catalyst (1 wt%), supported by the higher TON of 1 wt% Pt/NaX (TON = 14844) than 3 wt% Pt/NaX (TON = 5128). Effect of basic support with moderate (NaX) and strong (CHT) basic strengths are corelated for the higher cyclohexanone formation. Presence of strong basic sites and higher TON of 3 wt% C-HT (TON = 6806) directs the significant substrate-support interaction. Catalytic activity and recyclability are supported by the comparable performance of recycle runs and characterizations of the fresh and spent catalysts.
Keywords: aromatic monomers; Hydrogenation; lignin; Solid bases; supported metal catalyst; Upgradation